The Legacy of George and Geraldine Andrews for Mexico at Austin's Alexander Architectural Archives - Gilabert Sansalvador, Laura (Facultad de Arquitectura, Universidad Nacional Autónoma de México, 2020)
The George F. and Geraldine D. Andrews Collection, preserved at the University of Texas, Austin, contains a unique, extensive archive of field observations and research materials on Maya architecture. The online publication of a part of this collection provides global access to the work of the Andrews, who documented numerous buildings at hundreds of archaeological sites with the final goal of creating a large database on the Maya architectural heritage.